Blood, Faith and Iron - Belford, Paul (Archaeopress, 2018)
The Ironbridge Gorge is presented as the birthplace of the Industrial Revolution and so part of a national narrative of heroic Protestant individualism. However this is not the full story. This book asserts that this industrial landscape was, in fact, created by an entrepreneurial Catholic dynasty over 200 years before the Iron Bridge was built.